Sectoral changes of employment in Poland during the COVID-19 pandemic: Are reallocation shock effects applicable? - Kwiatkowski, Eugeniusz; Szymańska, Agata (Economics and Business Review, 2022)
The aim of this study is to analyse changes in employment and their determinants in twenty sectors of economic activity in Poland during the COVID-19 pandemic. The study focuses on the direct short-run employment effects. The changes in employment in the pandemic period (restricted to 2020q2–2021q2) with the changes in the pre-pandemic period (2015q1–2020q1) are compared. Statistics Poland and Eurostat are the sources of data. The analyses are based on quarterly and annual frequencies and cover the period from 2015q1 to 2021q2. Changes in employment are explained by the changes in gross value added, the differences in elasticities of employment with respect to the gross value added and the impact of the pandemic period. The results suggest that employment was affected by a reallocation shock—a decrease in employment that occurred in some sectors (e.g. arts, entertainment and recreation) was associated with an increase in other sectors (e.g. human health and social work activities).